2018
DOI: 10.1021/acsami.7b18729
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Decorated Mesoporous Silica for Biomineralization of Calcium Carbonate and P2 Purinergic Receptor-Mediated Antitumor Activity against Aggressive Lymphoma

Abstract: Adenosine triphosphate (ATP) is an important transmitter that mediates various biological effects via purinergic receptors (P2 receptors) in cancer. We investigated the antitumor activity of ATP-decorated and doxorubicin (DOX)-loaded mesoporous silica with biomineralization of calcium carbonate against a highly aggressive and metastatic murine lymphoma called Dalton's lymphoma (DL). Our results suggest that this nanocomposite has unique effects with respect to the morphology and properties of calcium carbonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Additional research showing a relationship between P2X7 and lymphoma concerns an aggressive and metastatic murine form of this neoplasm called Dalton's lymphoma (DL). The authors tested the antitumoral effect of silica particles carrying ATP plus doxorubicin and designed to target cancer in a pH-dependent fashion on DL growth and progression (Srivastava et al, 2018). Srivastava et al (2018) demonstrated a good efficiency of the particles in reducing lymphoma burden and increasing overall survival of lymphoma-bearing mice, suggesting that this effect will be mediated by upregulation of P2X7 receptor and consequent cytotoxicity.…”
Section: P2x7 and Lymphomamentioning
confidence: 99%
“…Additional research showing a relationship between P2X7 and lymphoma concerns an aggressive and metastatic murine form of this neoplasm called Dalton's lymphoma (DL). The authors tested the antitumoral effect of silica particles carrying ATP plus doxorubicin and designed to target cancer in a pH-dependent fashion on DL growth and progression (Srivastava et al, 2018). Srivastava et al (2018) demonstrated a good efficiency of the particles in reducing lymphoma burden and increasing overall survival of lymphoma-bearing mice, suggesting that this effect will be mediated by upregulation of P2X7 receptor and consequent cytotoxicity.…”
Section: P2x7 and Lymphomamentioning
confidence: 99%
“…Adenosine triphosphate (ATP), an existence form of energy, was found to mediate drug-liberating process during cancer therapy, and to be acted as an antineoplastic agent in vitro [76]. Based on this, S.P., et al (2018) [75] synthesized an ATP-loaded nanocomposite with pronounced apoptosis in tumor cells. First, mesoporous silica nanoparticles (MSNPs), a biocompatible deliver, was decorated with ATP on the surface.…”
Section: Cancer/tumor Target Engineeringmentioning
confidence: 99%
“…Srivastava et al developed adenosine triphosphate (ATP)‐functionalized MSNs with a calcium carbonate coating for cancer drug delivery against aggressive lymphoma ( Figure ) . ATP could serve as modulator ligand binding purinergic receptors (P2 receptors), which are overexpressed in diverse cancer cells types thus suppressing tumor cell growth.…”
Section: Ph‐responsive Drug Delivery Systemsmentioning
confidence: 99%